Assisting Local Farmers with Smart Agriculture Practices Using IoT Technology - Maq, Mumu Muzayyin (International Assulta of Research and Engagement (IARE), 2025)
This community service initiative aimed to improve agricultural practices in rural smallholder farming through the adoption of Internet of Things (IoT) technology for smart farming. The challenge in Desa Sukamaju, a region reliant on traditional farming methods, was the inefficient use of water and suboptimal crop yields, which were exacerbated by unpredictable weather patterns. The goal of this intervention was to empower local farmers by providing them with real-time data on soil moisture, temperature, and humidity to optimize irrigation and improve crop productivity. The approach adopted was Participatory Rural Appraisal (PRA), ensuring active farmer involvement in every phase of the program. The project utilized hands-on training to install and use IoT sensors, followed by continuous monitoring and support. Results showed a 23% reduction in water usage and an 18% increase in crop yields, particularly in vegetable crops. Additionally, qualitative feedback indicated a significant increase in farmer confidence, with 85% reporting greater technological competence. This indicates that IoT can significantly enhance resource management and crop productivity, even for farmers with limited digital experience. However, challenges such as the sustainability of technology maintenance and scalability were identified. The findings highlight the potential of IoT to modernize smallholder farming and underscore the need for continuous support and cost-effective solutions for long-term impact. The contribution of this work lies in demonstrating the practical, scalable application of IoT technology in rural farming settings, with recommendations for future projects to ensure sustainability and broader adoption.